2014
DOI: 10.1159/000369121
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Endovascular Treatment of Patients with Large Vessel Occlusion Presenting with Mild Symptoms: An Observational Multicenter Study

Abstract: Background: A significant proportion of stroke patients presenting with mild symptoms does not have a successful recovery, especially when a large vessel is occluded. IV thrombolysis is safe and may benefit patients presenting with mild symptoms. In this study, we tested whether endovascular therapy (ET) is superior to medical therapy in these patients. Methods: Observational, prospectively collected, multicenter study of 78 consecutive patients admitted from 2009 to 2012 within 6 h of stroke, with NIHSS ≤5 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 26 publications
6
60
3
Order By: Relevance
“…For the collateral grades being correlated with outcomes, 12 studies used the American Society of Intervention and Therapeutic Neuroradiology/Society of Interventional Radiology (ASITN/SIR) collateral flow grading system45 by digital subtraction angiography (DSA),2 9 17 18 27 31 32 37 38 42–44 mostly defining ASITN/SIR collateral grades of 3–4 and 0–2 as good and poor collaterals, respectively; 11 studies used other grading methods by DSA;12 14–16 22 25 26 33–35 39 9 studies used different grading methods on CT angiography (CTA);13 19 20 23 28 30 36 40 41 and the other studies used CT perfusion or combined grading methods with different imaging modalities 21 24 29…”
Section: Resultsmentioning
confidence: 99%
“…For the collateral grades being correlated with outcomes, 12 studies used the American Society of Intervention and Therapeutic Neuroradiology/Society of Interventional Radiology (ASITN/SIR) collateral flow grading system45 by digital subtraction angiography (DSA),2 9 17 18 27 31 32 37 38 42–44 mostly defining ASITN/SIR collateral grades of 3–4 and 0–2 as good and poor collaterals, respectively; 11 studies used other grading methods by DSA;12 14–16 22 25 26 33–35 39 9 studies used different grading methods on CT angiography (CTA);13 19 20 23 28 30 36 40 41 and the other studies used CT perfusion or combined grading methods with different imaging modalities 21 24 29…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, thorough imagingbased screening is likely to identify patients with large vessel occlusions but with only mild stroke severity. A previous observational study has suggested that endovascular treatment may offer little benefit to these patients [42] . However, it is unclear what impact penumbral imaging would have on patient selection and therefore patient outcomes.…”
Section: Looking Forwardmentioning
confidence: 97%
“…The prescribed time windows for IVT treatment were 7 h at most, being 3 or 4.5 h in a majority of studies, whereas the time window was unknown in several primary studies. Pre-treatment collateral status was assessed by various imaging modalities, half of which were single-or multi-phase CT angiography [8,12,[20][21][22][23][24][25][26][27][28][29][30][31][32], others being CT or MR perfusion imaging [7,13,17,19,33,34], fluid-attenuated inversion recovery imaging [14,16,18,35], digital subtraction angiography [29,36], etc. Fourteen (1584 patients) of the 28 studies were included in the quantitative meta-analysis.…”
Section: Study Selection and Descriptionmentioning
confidence: 99%